Role of public-private partnerships to enhance the health care delivery system during the pandemic COVID-19 - Indurthy, Sindhu Gayathry; Kashyap, Gyan Chandra (International Journal Of Community Medicine And Public Health, 2020)
Development and economic growth are based on a healthy nation. A lot of attentions are needed to improve health conditions by providing necessary facilities through better infrastructure and medical professionals. Public health facilities continue to face staff shortage as over 85% specialist doctors, 75% doctors, 80% laboratory technicians, 53% nursing, and 52% ANM (auxiliary nurse midwife) short across states.At the same time when the prevalence of infectious diseases has increased worldwide over a period. Outbreaks have frequently been occurring, but every outbreak does not reach global pandemic level as the novel coronavirus (COVID-19) has. Although the number of COVID-19 cases are gradually increasing in India, experts have warned that this spread will lead to a rapid and massive increase in demand for health facilities. India's healthcare infrastructure is incapable of dealing with today’s crisis. In India, there is a significant shortage in the availability of beds in hospitals. It is only in recent years that India increased its bed capacity from 0.7 beds per thousand, in 2011, to 1.13 today. According to data from the National Health Profile-2019, we observed there are 7,13,986 total government hospital beds available in India; however, it is still insufficient to deal with this crisis. There are only 118 governments approved laboratories in India capable of performing COVID-19 tests so far.